2005
DOI: 10.1136/jcp.2004.022103
|View full text |Cite
|
Sign up to set email alerts
|

High co-prevalence of genogroup 1 TT virus and human papillomavirus is associated with poor clinical outcome of laryngeal carcinoma

Abstract: Background: The aetiology and factors leading to the progression of laryngeal cancer are still unclear. Although human papillomavirus (HPV) has been suggested to play a role, reports concerning the effect of HPV infection on tumour development are controversial. Recently, transfusion transmitted virus (TTV) was suggested to play a role in certain infections as a causative or coinfecting agent. Aims: To investigate whether the development and progression of laryngeal squamous cell carcinoma is associated with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 24 publications
2
33
1
1
Order By: Relevance
“…Compared to oral carcinomas, a greater diversity of other HPV types has been detected: HPV18, HPV26, HPV31, HPV33, HPV39, HPV36, HPV45, HPV51, HPV52, HPV58, HPV59, HPV66, and HPV69 [8,9,14,20,26,29,39,65,71,90,94]. Low-risk HPV are uncommonly detected, and might represent incidental ''bystander'' rather than possibly ''driver'' infection [29,39,65,75,90,94].…”
Section: Hpv and Cancers Of The Larynxmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to oral carcinomas, a greater diversity of other HPV types has been detected: HPV18, HPV26, HPV31, HPV33, HPV39, HPV36, HPV45, HPV51, HPV52, HPV58, HPV59, HPV66, and HPV69 [8,9,14,20,26,29,39,65,71,90,94]. Low-risk HPV are uncommonly detected, and might represent incidental ''bystander'' rather than possibly ''driver'' infection [29,39,65,75,90,94].…”
Section: Hpv and Cancers Of The Larynxmentioning
confidence: 99%
“…Low-risk HPV are uncommonly detected, and might represent incidental ''bystander'' rather than possibly ''driver'' infection [29,39,65,75,90,94]. Rarely, integrated low-risk HPV has been found; viral integration does suggest viral-mediated carcinogenesis [90,94]. Head and Neck Pathol (2012) 6:S104-S120 S109 …”
Section: Hpv and Cancers Of The Larynxmentioning
confidence: 99%
“…Similarities of prevalence of TTV between patients with and without infection by H pylori, and prevalence of H pylori between patients with and without infection by TTV, as well as the discrepancy in age distributions between prevalence of TTV and H pylori in our patients with peptic ulcer disease indicate that no correlation exists between TTV and H pylori infection, even though the two agents have similar age distributions in the general population and similar routes of transmission have been suggested for the two agents [115] . According to one report, the high prevalence of genogroup 1 TT virus infection in patients with laryngeal cancer and its striking co-prevalence with human papilloma virus infection is biologically important in the progression of squamous cell carcinoma of the larynx [116] . TTV might replicate in the respiratory tract [117] .…”
Section: Ttv Coinfectionmentioning
confidence: 99%
“…Cofactors that modify the risk in HPV DNA positive women include the use of oral contraceptives for five or more years, smoking, high parity and previous exposure to other sexually transmitted diseases (Bosch and de Sanjose 2007). Szladek et al (2005) reported that coinfection with a virus named Torque Teno Virus (TTV), belonging to genogroup 1 and HPV promoted the progression of squamous cell carcinoma of the larynx and was associated with an unfavorable prognosis. This TT Virus was first described in the patients with posttransfusion hepatitis by Nishizawa et al (1997) who designated this agent as TTV after the initials of the patient in whom it was discovered.…”
Section: Introductionmentioning
confidence: 99%